2011
DOI: 10.1111/j.1540-8159.2010.03022.x
|View full text |Cite
|
Sign up to set email alerts
|

The QRS Narrowing Index Predicts Reverse Left Ventricular Remodeling Following Cardiac Resynchronization Therapy

Abstract: After adjusting for potential confounders, QRS narrowing, indexed to baseline QRS duration, is associated with enhanced reverse ventricular remodeling following CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 28 publications
3
57
1
Order By: Relevance
“…18,19) Increasing SS of LV pacing in CRT captures an enlarged myocardial area and provides a pacing response beyond a discrete region with conduction block, which thereby leads to more rapid electrical conduction in comparison with baseline. [7][8][9][10] This effect appears prominently in low-amplitude areas of electroanatomic voltage maps, such as infarct borders. 20) Recently, Tedrow, et al demonstrated that increasing SS of LV pacing in CRT reduces inter-ventricular conduction time and QRS duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19) Increasing SS of LV pacing in CRT captures an enlarged myocardial area and provides a pacing response beyond a discrete region with conduction block, which thereby leads to more rapid electrical conduction in comparison with baseline. [7][8][9][10] This effect appears prominently in low-amplitude areas of electroanatomic voltage maps, such as infarct borders. 20) Recently, Tedrow, et al demonstrated that increasing SS of LV pacing in CRT reduces inter-ventricular conduction time and QRS duration.…”
Section: Discussionmentioning
confidence: 99%
“…7) If the capture of an enlarged myocardial area extends beyond a discrete region with conduction block, the increasing SS of LV pacing could provide more rapid electrical conduction in comparison with baseline. [8][9][10] Recent CRT studies have demonstrated that increasing SS of LV pacing reduces QRS duration on electrocardiograms (ECG). 10,11) The present study aimed to investigate whether increasing SS of LV pacing could improve LV mechanical dyssynchrony and cardiac function in patients treated with CRT.…”
mentioning
confidence: 99%
“…It is useful to know whether the QRS duration can be shortened when predicting the possibility of left ventricular structural remodeling or developing a prognosis for patients receiving CRT. [4][5][6][7] Moreover, the results of several small scale studies and also a case report have suggested that CRT can reverse ventricular electrical remodeling. [8][9][10][11] It is currently hypothesized that successful reverse structural remodeling of the left ventricle during cardiac resynchronization therapy may induce improved ventricular electrical conduction in heart failure patients without the need for pacing the dual ventricular chambers.…”
Section: T He Efficacy Of Cardiac Resynchronization Therapy (Crt)mentioning
confidence: 99%
“…However, up to one third of patients do not respond to CRT. In that regard, few initial studies presenting multisite pacing have shown encouraging results [2], demonstrating both feasibility and safety in placing a second CS lead in >80% of patients intended, with further QRS shortening, which is the most powerful predictor of LV reverse remodeling [3]. Such optimization of the resynchronization therapy might be able to improve the percentage of responders to CRT when applied to selected patients.…”
Section: Introductionmentioning
confidence: 99%